How to assess repeatability and reproducibility of a mechanical test? An example for sports engineers - Krumm, D.; Schwanitz, S.; Odenwald, S. (Proceedings, 2020)
Several sources of variation can affect the performance of a mechanical test. Hence, the measurement system performance should be assessed. The gage repeatability and reproducibility study is a method used to assess and quantify the variation of a mechanical test. Since it seems that this method has not yet found its way into the field of sports engineering, this paper promotes its application by demonstrating a practical example based on a current problem in sports shoe development. In detail, a novel mechanical simulation to determine the forefoot bending stiffness of athletic footwear during plantar flexion movement was developed and its quality assessed. The ANOVA Gage R&R study was performed based on 64 randomized trials of eight footwear samples assessed by two appraisers. The mechanical test was evaluated as acceptable for the desired application and the resolution was quantified to be 0.04 Nm/°.